Switching to "lighter" cigarettes and quitting smoking. Issue 6 (4th November 2009) - Tindle, H A; Shiffman, S; Hartman, A M; Bost, J E
Abstract : Objective: Smokers who switch to "lighter" cigarettes may be diverted from quitting smoking. We assessed factors associated with switching and the association between switching and (1) making a quit attempt, and (2) recent quitting, yielding a measure of net quitting (attempts × recent quitting). Design: In 2003, a total of 30 800 ever-smokers who smoked in the past year provided history of switching and 3 reasons for switching: harm reduction, quitting smoking and flavour. Among those who made a past-year quit attempt, recent quitting was defined as ⩾90-day abstinence when surveyed. Multivariable logistic regression identified determinants of outcomes. Results: In all, 12 009 (38%) of ever-smokers switched. Among switchers, the most commonly cited reasons were flavour only (26%) and all 3 reasons (18%). Switchers (vs non-switchers) were more likely to make a quit attempt between 2002 and 2003 (51% vs 41%, p<0.001, adjusted odds ratio (AOR) 1.58, (95% confidence interval (CI) 1.48 to 1.69)), but less likely to have recently quit (9% vs 17%, p<0.001; AOR 0.40 (95% CI 0.35 to 0.45)), yielding lower overall net quitting (4.3% vs 7.0%, p<0.001; AOR 0.54, (95% CI 0.47 to 0.61)). The effects of switching on outcomes were most pronounced for reasons including quitting smoking, whereas switching for harm reduction alone had no association with outcomes. Conclusion: Compared with no switching, a history of switching was associated with 46% lower odds of net quitting.